2021
DOI: 10.1111/asap.12259
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and coping strategies during the COVID‐19 pandemic: A qualitative study of unemployed and employed people in Nigeria

Abstract: The coronavirus disease 2019 (COVID-19) significantly disrupted human activities all over the world. Despite this, little or nothing is known about mental health and coping strategies during the COVID-19 pandemic among the unemployed and employed people in Nigeria. Therefore, this study was an effort towards bridging this knowledge gap. We employed a qualitative design with 66 participants (age range = 18-62 years) who described how the COVID-19 pandemic affected their mental health and how they coped during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…In addition, people in the 25–54-year-old age group were significantly more likely to report participating in subsistence activities compared to people in all other age groups in survey 2 (March 2021), which indicates that this age group is more likely to engage in these activities compared to older or younger adults. Other studies conducted during the pandemic, including in the US, Africa, Europe, and East Asia, have also shown the importance for men and women of spending time outside in gardens, parks, or other green spaces for improved wellbeing and helping unwind from additional pressures brought on by the pandemic [ 34 , 38 , 39 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, people in the 25–54-year-old age group were significantly more likely to report participating in subsistence activities compared to people in all other age groups in survey 2 (March 2021), which indicates that this age group is more likely to engage in these activities compared to older or younger adults. Other studies conducted during the pandemic, including in the US, Africa, Europe, and East Asia, have also shown the importance for men and women of spending time outside in gardens, parks, or other green spaces for improved wellbeing and helping unwind from additional pressures brought on by the pandemic [ 34 , 38 , 39 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found the general community fearful and critical of government guidelines around social distancing and isolation. [46][47][48][49][50] Despite self-adherence to these guidelines, lack of adherence by others triggered a lack of trust in governmental enforcement efforts. 46…”
Section: General Communitymentioning
confidence: 99%
“…The coronavirus disease 2019 continues to threaten the world since its first report in Wuhan, China in December 2019. As the COVID-19 is now a pandemic and continues to threaten global health (Chen et al, 2020;Coulthard, 2020;Cuschieri, 2020;Dodd et al, 2020;Ogueji et al, 2021aOgueji et al, , 2021bQian & Jiang, 2020;Robinson & Daly, 2020;Robles-Bello et al, 2020;Shaaban et al, 2020;Williams et al, 2020;World Health Organization, 2020), clinical trials have been ongoing to develop vaccines against the disease (Bokemper et al, 2020;Danchin et al, 2020;Giubilini, 2020;Haynes et al, 2020;Kaur & Gupta, 2020;Lazarus et al, 2020;McClung et al, 2020;Pogue et al, 2020;Su et al, 2020;Verger & Dubé, 2020;Zhu et al, 2020). According to the media report, many countries have implemented a vaccine distribution plan that prioritized at-risk groups, such as the elderly population (Beaumont, 2020).…”
Section: Introductionmentioning
confidence: 99%